The Popular Imagination in the Sculpture of Muhammed Ghani Hikmat (Al-Academy, 2023)
Talking about the importance of the imagination in sculptural works has a role in shaping the collective memory and moving it, whether it is an artistic, social, religious or historical imagination. Because it documents the cultural heritage of any country through the structural structure of the sculptural form, and its connotations and symbols, which are considered an effective aesthetic image in the crystallization of various intellectual concepts and contents.Therefore, the study aimed to know the employment of the popular imagination in the artistic works of the sculptor (Muhammad Ghani Hikmat), as well as to reveal the artistic and aesthetic features of the folklore and its reflection on its artistic style. And the references of the artwork, and in light of the above, the two researchers reached a set of results, the most important of which are: the ability of the artist, through the connotations and symbols inspired by the popular imagination, to bring back to mind the traditional stories and legends as a circulating collective discourse, and also the works of the artist who are aware of his cultural heritage reflect the extent of his ability to spontaneously narrate stories The collective popular imagination by adapting the material in an authentic and contemporary expressive artistic style, The sculptural edifices of (Muhammad Ghani Hikmat) appeared in a balanced manner through the mass with a regular rhythm, which gave the formative structure an expressive value in harmony with the space, and became a clear relationship with it.